2009
DOI: 10.1186/1471-2407-9-341
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of frozen section analysis in ultrasound- guided core needle biopsy of breast lesions

Abstract: BackgroundLimited data are available to evaluate the accuracy of frozen section analysis and ultrasound- guided core needle biopsy of the breast.MethodsIn a retrospective analysis data of 120 consecutive handheldultrasound- guided 14- gauge automated core needle biopsies (CNB) in 109 consecutive patients with breast lesions between 2006 and 2007 were evaluated.ResultsIn our outpatient clinic120 CNB were performed. In 59/120 (49.2%) cases we compared histological diagnosis on frozen sections with those on paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In another prospective cohort study, with a sample of 120 CNBs of palpable and impalpable tumors suspicious of breast cancer, the authors compared the frozen section technique with paraffin and suggested that frozen section showed good accuracy and enabled earlier diagnosis of breast cancer. The results were: sensitivity 95%, specificity 100%, PPV 100% and NPV 90% 24 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…In another prospective cohort study, with a sample of 120 CNBs of palpable and impalpable tumors suspicious of breast cancer, the authors compared the frozen section technique with paraffin and suggested that frozen section showed good accuracy and enabled earlier diagnosis of breast cancer. The results were: sensitivity 95%, specificity 100%, PPV 100% and NPV 90% 24 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Core needle biopsy (CNB) and fine needle aspiration cytology (FNA) are well-established methods for characterizing breast lesions [28][29][30][31]; however, both methods are invasive and relatively expensive. In addition to mammography, US has become a standard non-invasive diagnostic imaging method used for the detection of breast cancer, particularly in the dense breast [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of cytological techniques for determining the nature of sono-or mammographically diagnosed breast abnormalities, percutaneous image-guided core needle biopsy has become an alternative to surgical biopsy for the histological assessment of breast lesions (13). However, intraoperative frozen section pathology is widely used in numerous countries, including China.…”
Section: Discussionmentioning
confidence: 99%